Antianginal Therapy for Stable Ischemic Heart Disease: A Contemporary Review. (November 2017) - Padala, Santosh K.; Lavelle, Michael P.; Sidhu, Mandeep S.; Cabral, Katherine P.; Morrone, Doralisa; Boden, William E.; Toth, Peter P.
Chronic angina pectoris is associated with considerable morbidity and mortality, especially if treated suboptimally. For many patients, aggressive pharmacologic intervention is necessary in order to alleviate anginal symptoms. The optimal treatment of stable ischemic heart disease (SIHD) should be the prevention of angina and ischemia, with the goal of maximizing both quality and quantity of life. In addition to effective risk factor modification with lifestyle changes, intensive pharmacologic secondary prevention is the therapeutic cornerstone in managing patients with SIHD. Current guidelines recommend a multifaceted therapeutic approach with β-blockers as first-line treatment. Another important pharmacologic intervention for managing SIHD is nitrates. Nitrates can provide both relief of acute angina and can be used prophylactically before exposure to known triggers of myocardial ischemia to prevent angina. Additional therapeutic options include calcium channel blockers and ranolazine, an inhibitor of the late inward sodium current, that can be used alone or in addition to nitrates or β-blockers when these agents fail to alleviate symptoms. Ranolazine appears to be particularly effective for patients with microvascular angina and endothelial dysfunction. In addition, certain antianginal therapies are approved in Europe and have been shown to improve symptoms, including ivabradine, nicorandil, and trimetazidine; however, these have yet to be approved in the United States. Ultimately, there are several different medications available to the physician for managing the patient with SIHD having chronic angina, when either used alone or in combination. The purpose of this review is to highlight the most important therapeutic approaches to optimizing contemporary treatment in response to individual patient needs.